Monetary policy of the National Bank of Kazakhstan in the context of cyclic economic development (Journal of Economic Research & Business Administration, 2018)
The article explores the monetary policy of the National Bank of Kazakhstan in the context of cyclicaleconomic development. In recent years there has been a decline in the ranking of Kazakhstan in theglobal competitiveness index, primarily in the position «Macroeconomic Environment» that covers suchimportant indicators as inflation, budget deficit and external debt, which characterize the stability andpredictability of the fiscal and monetary policy, as well as the state of the economy.The purpose of this study is to develop recommendations to improve the effectiveness of monetarypolicy, strengthen the supervisory functions of the National Bank of Kazakhstan regarding the activitiesof second-tier banks and increase the responsibility of commercial banks’ leadership for their financialcondition.Sustainable macroeconomic development is the basis for the development of financial markets thatstimulates the productivity and national competitiveness in the long run. At the same time, the globalcompetitiveness index is a practical tool for setting key tasks and assessing the effectiveness of the nationalgovernment.Based on the results of the conducted studies, key features and problems of the development of thenational economy are identified in the face of new challenges and threats, close integration and dependencefrom the development of the world economy. Recommendations are proposed for improving theefficiency of monetary policy in the context of cyclical economic development of Kazakhstan in order toensure the macroeconomic stability in an effort for Kazakhstan to achieve the strategic task of enteringtop 30 developed countries.The basis of the study is a systematic approach, a dialectical method of cognition, as well as logicalanalysis and synthesis.The results of the research demonstrate a high degree of dependence of the rates of financial marketdevelopment on the macroeconomic environment. All macroeconomic factors (fiscal and monetary policy,structural and investment policy, strategy of public debt management, level of welfare and savings)affect the stability and development trends of financial markets. Since financial markets are indicators ofthe state of the economy, the formation of a stable and steadily developing macroeconomic environmentis an objective necessity both for improving Kazakhstan’s competitiveness and developing the country’sfinancial market to ensure efficient access to financial resources.The National Bank of Kazakhstan should move more quickly to increased risk-based supervision,the aim of which is to stimulate the highly prudent policy of second-tier banks, as the financial regulatorwas late with a real solution to the problems of the banking sector that piled up in the wake of theglobal financial crisis of 2008-2009. For instance, 90% of the bad debt portfolio was issued by banks in the period from 2006 to 2015. The greatest abuse in the misuse of money by second-tier banks wasobserved during this period. After the crisis of 2009, when banks lost the opportunity to attract loansfrom abroad, they began to raise significant amounts of money from the quasi-public sector. The amountof public funds on bank accounts within several years increased from 2.5 trillion tenge to 7 trillion tenge,and banks used this money at their discretion without a balanced credit policy aimed at lending to thereal sector in order to achieve the strategic national task of accelerated economic and technologicalmodernization and entry into top 30 developed countries.To address the above problems, specific recommendations were proposed to the Government andthe National Bank of Kazakhstan to reduce inflation and improve the banking sector.Practical significance of the results of the work. The reduction in the rate of inflation, which isachieved through the implementation of monetary and credit policy, is of great practical importancefor ensuring macroeconomic stability. In addition, reduced inflation contributes to the development ofbusinesses, since price stability helps entrepreneurs to more confidently decide on the issues of mediumtermplanning and financing of the real sector of the economy. Affordable lending should be the key tomass entrepreneurship.